Opini Wajar di Tengah Skandal: Sejauh Mana Efektivitas SA 330 dalam Merespons Risiko Kecurangan pada PT Indofarma Tbk? Opini Wajar di Tengah Skandal: Sejauh Mana Efektivitas SA 330 dalam Merespons Risiko Kecurangan pada PT Indofarma Tbk? - Mutiara Anita (Benefits : Jurnal Ekonomi dan Pariwisata Internasional, 2026)
This study evaluates the implementation of Audit Standard (SA) 330 by auditors regarding fraud risks at PT Indofarma Tbk. Despite irregularities totaling IDR 471.83 billion and chronic financial distress, the entity maintained Unqualified Opinions for the 2021–2022 period. This study presents novelty through a three-dimensional triangulation approach—empirical, academic, and professional standards—to analyze audit technical evaluation. Using a descriptive qualitative method based on documentation study, the findings indicate that the implementation of the auditor's response was not fully optimal in mitigating material risks. Key findings reveal a potential weakening of professional skepticism and inappropriate nature, timing, and extent of audit procedures in detecting receivable manipulations and off-balance sheet liabilities (online loans). This study concludes that the audit's failure to bridge information asymmetry left material risks undetected until a public financial crisis emerged.